Além da marcha: a (re) formação da coluna Miguel Costa - Prestes - Castro, Maria Clara Spada de [UNIFESP] (2016)
By using the correspondence exchanged between the rebels, this research aims to understand how was the Miguel Costa?Prestes? Column formed starting from the tenentism movements that preceded it, like the uprising in 1922 in Rio de Janeiro and the revolts in 1924 in many states, such as São Paulo, Sergipe, Amazonas and Rio Grande do Sul. The analyses sought to verify a continuity on the tenentism movement between 1922 to 1927, what was its social origins and the political perspectives of the main leaders, proposing different interpretations from the ones already consolidated by the historiography.